Mixed epithelial and stromal tumour of the kidney with luteinised ovarian stroma. Issue 1 (9th January 2007) - Buritica, C; Serrano, M; Zuluaga, A; Arrabal, M; Regauer, S; Nogales, F F
Abstract : We report a case of a 9-cm mixed epithelial and stromal tumour of the kidney in an obese 70-year-old woman with diabetes. The ovarian-type stroma had a spindle cell component that was positive for progesterone receptors and had the hitherto unreported presence of abundant foci of luteinised stromal cells with characteristic immunohistochemical positivity to α-inhibin, calretinin, aromatase and gonadotropin-releasing hormone (GnRH) receptors. We conclude that the stromal component is identical to ovarian cortical stroma. We believe that ovarian-type stroma occurs in extragenital tumours as a result of an epithelial–stromal interaction in an environment of hormonal hyperstimulation.